Construction of enterprise digital service and operation platform based on internet of things technology - Qianying Gao; Qi Wang; Cisheng Wu (Journal of Innovation & Knowledge (JIK), 2023)
The enterprise digital service and operation platform is a national-level platform for operating digital content in the field of standardisation. Based on the national standards for enterprise digital service products, this platform develops a digital product library of standard resource content. The construction of a public operation platform will provide standard digital products and personalised services for individuals and institutional users. The concept of Internet of Things technology is constantly evolving from 'smart earth' in the United States to the 'perceived China' in China. However, no unified definition has been reached thus far. This study examined the construction of enterprise digital service and operation platforms based on the Internet of Things technology. Under the same conditions, the peak value of the data processing efficiency of a single thread in the asynchronous architecture was approximately 4,200 pieces, whereas that in the synchronous architecture was approximately 1,200 pieces. The processing performance of the asynchronous architecture is improved by 320% relative that of the synchronous architecture. As a global dynamic network, the Internet of Things technology can realise intelligent identification, positioning, monitoring, and other functions through specific equipment, sensors, and information processing technologies. It is based on the Internet and has thus been extended and expanded.
Keywords: 650; Internet of Things technology; Enterprise digital service; Operation platform construction